2011
DOI: 10.1179/1743289810y.0000000023
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional numerical modelling of discontinuous fibre composite architectures

Abstract: A three-dimensional geometrical model is presented for generating discontinuous random fibre architectures consisting of high filament count bundles. The fibre network model randomly distributes fibre bundles in a three-dimensional volume using a non-contact algorithm, together with Catmull-Rom spline interpolation, to provide a physically representative material. Only the spines of the fibre bundles are modelled, using truss elements to permit high fibre volume fractions of up to 60%, with no restriction on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Thus, nonover-lapped out-of-plane geometric models have the potential to be most realistic. In this regards the work of Luchoo et al [29] was a good initial effort. He proposed a non-contact algorithm and spline interpolation to generate 3D architecture of fibre bundles.…”
Section: Geometric Modelling Strategies Of Dfc Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, nonover-lapped out-of-plane geometric models have the potential to be most realistic. In this regards the work of Luchoo et al [29] was a good initial effort. He proposed a non-contact algorithm and spline interpolation to generate 3D architecture of fibre bundles.…”
Section: Geometric Modelling Strategies Of Dfc Materialsmentioning
confidence: 99%
“…The work of LT Harper et al [30] significantly improved the earlier model and [29] used a force-directed algorithm to generate 3D architecture of DFC material. The author's considered out-of-plane orientation, bending and twisting of fibres bundles, and successfully generated RVE of small fibre bundles (3k having 1.7 mm width) with volume fraction close to 50%.…”
Section: Geometric Modelling Strategies Of Dfc Materialsmentioning
confidence: 99%
“…Pan et al [29] used Halpin-Tsai predictions to benchmark the FEA stiffness results, indicating relative errors of 5.8% and 12% for the tensile and shear moduli respectively. Ignoring fibre curvature can artificially increase the predicted UTS values by up to 18% [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Additional dummy sister nodes are added at each bundle end to provide the minimum number of points required for spline interpolation for bundles that have been cropped at the RVE boundary [39]. The implementation of the spline interpolation algorithm is discussed in detail in [31]. It should be noted that spline interpolation can introduce further edge-edge and edge-surface intersections, which increase in numbers as the curvature of the edge increases.…”
Section: Spline Interpolation Algorithmmentioning
confidence: 99%
“…It has been studied by many authors for randomly distributed fiber bundles, Servais et al suggested an experimental method to measure the packing stress up to 100 kPa (i.e., low normal stress). Luchoo et al simulated the elastic response at the mesoscale. Hereunder, we consider that normal stresses (6–12 MPa) involved while press forming ROS is way higher than the packing stress and that the fiber bed is fully compacted.…”
Section: Introductionmentioning
confidence: 99%